A retrospective review of complications in a South African neurocritical care unit over one year - Kgaodi, Bakang Abiot (Division of General Surgery, 2024)
Background: The establishment of a Neurocritical Care Unit (NCCU) is well described in offering benefits to patients1,2. These units are optimised to care for patients with pathologies involving the brain and spine. Complications peculiar to such units in Low- and Middle-income countries (LMICs) are relatively undocumented. Objectives: To determine the complications in a NCCU at Groote Schuur Hospital (GSH) over 1 year and their association with ICU length of stay (LOS) and mortality. Methods: A retrospective review of complications of patients admitted to the NCCU at GSH from 01 January 2020 to 31 December 2020 as per NCCU patient data registry (HREC: R012/2015). Results: 850 patients, predominantly males (61.2% for HC and 68.1% for ICU), were admitted to the NCCU with a median age of 43 years (HC) and 41 years (ICU). The overall complication incidence rate was 38.2%. The statistically significant complications (p-value <0.05) were metabolic and electrolyte abnormalities as well as infection (including VAPs, SSIs and CLABSIs) and DVTs. The most common complication was metabolic abnormalities (28.2%), specifically derangements in sodium homeostasis. LOS was shown to have a statistically significant association with number of complications. Mortality did not have a statistically significant association with number of complications. Conclusion: Complications in a dedicated NCCU in South Africa are mostly electrolyte disturbances and infections. The complications are associated with increased LOS but not with increased risk of mortality.